STUDI PENGARUH JUMLAH SUDU TERHADAP UNJUK KERJA SAVONIUS WATER TURBINE PADA ALIRAN AIR DALAM PIPA - Imron Hamzah; Syamsul Hadib; D. Danardono Dwi Prija Tjahjanac (ROTOR, 2016)
Rainwater, flowed through a pipe, has potential energy that can be used to drive a turbine coupled with generator. Savonius water turbine with horizontal axis is used here as the turbine. The research compares the Savonius water turbine with different blade number of 2, 4, 6, 8, 10 and 12 using Computational Fluid Design (CFD) of SolidWork 2013. The turbine specifications have the angle of curvature about 70°, the aspect ratio of 1, the end plate ratio of 1,1 and deflector angle of 45°. The data obtained in this paper are the pressure contour of Savonius turbine blade, the velocity of fluid flow and the torque generated. The aims of the research are to obtain the influence of the blade number in the Savonius turbine to the turbine performances and to obtain the best of blade number. The results show that two blades has the best performances compared with the others. It has the highest torque about 5,75 Nm for the same conditions as well. Keywords: power, Savonius turbine, torque, blade, flow